Development of The Halal Industry in Indonesia: The Role of Sharia Rural Bank - Riskiyatul Khasanah; Nur Azizah (Universitas Trunojoyo Madura, 2022)
This study scrutinizes the role of Sharia Rural Banks in encouraging the development of the halal industry in Indonesia through the influence of credit disbursement and third-party funds collected by Sharia Rural Banks (BPRS). The halal industry has significant potential and requires financing based on sharia principles to create a synergy between the halal industry and sharia finance. BPRS sees a high priority in assisting the development of the halal industry because it is intended for the general public and small entrepreneurs who are not accessible to commercial banks. The research methodology employed in this study is quantitative, using multi-linear regression analysis (Ordinary Least Square) to determine the relationship between the credit disbursement of BPRS as well as third-party funds and the development of the halal industry in Indonesia. The results of the study indicate that the credit disbursement and the third-party funds collected by the BPRS have a significant role in the growth of the halal industry in Indonesia. This study advised more adaptive training in the future.